WWOX gene is associated with HDL cholesterol and triglyceride levels - Sáez, María E (BioMed Central, 2010)
BACKGROUND: Altered lipid profile, and in particular low HDL and high triglyceride (TG) plasma levels, are within the major determinants of cardiovascular diseases. The identification of quantitative trait loci (QTL) affecting these lipid levels is a relevant issue for predictive purposes. The WWOX gene has been recently associated with HDL levels. This gene is located at chromosome 16q23, a region previously linked to familial combined hyperlipidemia (FCHL) and HDL. Our objective is to perform a genetic association analysis at the WWOX gene region with HDL, TG and TG/HDL ratio. METHODS: A quantitative association analysis performed in 801 individuals selected from the Spanish general population. RESULTS: For HDL levels, two regions of intron 8 display clustering of positive signals (p < 0.05) but none of them was associated in the haplotypic analysis (0.07 ≤ p ≤ 0.165). For TG levels not only intron 8 but also a 27 kb region spanning from the promoter region to intron 4 are associated in this study. For the TG/HDL genetic association analysis, positive signals are coincident with those of the isolated traits. Interestingly, haplotypic analysis at the 5' region showed that variation in this region modified both HDL and TG levels, especially the latter (p = 0.003). CONCLUSIONS: Our results suggest that WWOX is a QTL for both TG and HDL.